2018
DOI: 10.1111/1748-5967.12325
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Potential Distribution of an Invasive Species, Solenopsis invicta Buren (Hymenoptera: Formicidae), under Climate Change using Species Distribution Models

Abstract: The red imported fire ant is considered one of the most notorious invasive species because of its adverse impact on both humans and ecosystems. Public concern regarding red imported fire ants has been increasing, as they have been found seven times in South Korea. Even if red imported fire ants are not yet colonized in South Korea, a proper quarantine plan is necessary to prevent their widespread distribution. As a basis for quarantine planning, we modeled the potential distribution of the red imported fire an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 38 publications
4
55
0
Order By: Relevance
“…In recent years, invasion of alien species has gradually increased in Korea. However, in most of the cases, the controls over the invasive species were not successful, and various damages are rapidly increasing through the nationwide spread [49][50][51][52]. However, in some cases, the control of alien species is made when the valuable utilization of the invasive species as a potential resource are discovered [53].…”
Section: Amino Acidsmentioning
confidence: 99%
“…In recent years, invasion of alien species has gradually increased in Korea. However, in most of the cases, the controls over the invasive species were not successful, and various damages are rapidly increasing through the nationwide spread [49][50][51][52]. However, in some cases, the control of alien species is made when the valuable utilization of the invasive species as a potential resource are discovered [53].…”
Section: Amino Acidsmentioning
confidence: 99%
“…The maximum entropy modeling (MaxEnt) is widely used in the prediction of potential distribution of species in the context of climate change, environmental factor detection and risk assessment of invasive species (Adhikari et al, 2012;Yang et al, 2013;Fandohan et al, 2015;Sung et al, 2018;Chen et al, 2019), based on geographical distribution data and a variety of environmental data. Compared with other models, the MaxEnt has the advantages of less sample size, less influence by sample deviation and better accuracy (Elith et al, 2011;Kramer-Schadt et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Wetterer () documents the spread of S. invicta from its native South America across the southern United States and north‐eastern Mexico, through the West Indies and to New Zealand, Australia and parts of Asia. Several studies have used climate modeling based principally on temperature and rainfall parameters to predict the potential global range expansion of S. invicta and concluded that many additional regions in both the New World and the Old World are at risk of colonization by this pest (Korzukhin et al 2001; Morrison et al ; Sutherst and Maywald ; Sung, Kwon, Lee, & Cho, ). Under climate change scenarios modeled by Bertelsmeier et al () the potential distribution of S. invicta is predicted to increase in all regions.…”
Section: Introductionmentioning
confidence: 99%